2019
DOI: 10.1002/clc.23324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exergaming in postmenopausal women with high cardiovascular risk: A randomized controlled trial

Abstract: Objective Recently, exergames have been used an exercise modality as aerobic fitness activities. However, evidence of its effectiveness on cardiovascular (CV)‐related risk factors remain unclear. Hypothesis We evaluate the effects of exergaming on CV‐related risk factors compared with traditional aerobic exercise in high CV risk patients. Methods Sixty‐five postmenopausal women with high CV risk were randomized among exergame (n = 22), treadmill (n = 22), and control (n = 21) groups. The exergame group was eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 29 publications
0
63
0
Order By: Relevance
“…When data were provided as intervention effects and/or using other measures of dispersion (e.g., standard error, 95% confidence intervals), the required information was estimated following the guidelines available elsewhere. 34 A specific software (WebPlotDigitizer 4.2, San Francisco, CA) was used to extract data when provided as a figure, 22,24,26 and we contacted the authors of two studies because the required data had not been reported for the control group. 27,28 However, the authors of one study 28 could not be contacted and thus we were unable to include their data in quantitative synthesis-the study was nevertheless included in the qualitative results.…”
Section: Data Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…When data were provided as intervention effects and/or using other measures of dispersion (e.g., standard error, 95% confidence intervals), the required information was estimated following the guidelines available elsewhere. 34 A specific software (WebPlotDigitizer 4.2, San Francisco, CA) was used to extract data when provided as a figure, 22,24,26 and we contacted the authors of two studies because the required data had not been reported for the control group. 27,28 However, the authors of one study 28 could not be contacted and thus we were unable to include their data in quantitative synthesis-the study was nevertheless included in the qualitative results.…”
Section: Data Extractionmentioning
confidence: 99%
“…All were conducted in individuals who had, on average, overweight or obesity (body mass index >25 kgÁm −2 ), with mean age ranging from 23 to 68 years. However, other participants' characteristics differed across studies, with four of them specifically conducted in individuals with overweight or obesity, [27][28][29]31 two in individuals with metabolic syndrome, 23,30 one in individuals with high CVD risk (e.g., Framingham 10-year risk score >20%), 24 one in patients on hemodialysis, 22 one in individuals with depressive disorders, 26 and one combining people who were healthy and individuals with defective glucose tolerance. 25 Exercise interventions were supervised in all cases and included three sessions per week ($30-60 min per session) in the majority of cases except for one study, in which training frequency was not specified.…”
Section: Studies' Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations